Zawód nauczyciela w Polsce – wybrane aspekty - Michalak-Dawidziuk, Joanna (Studia Edukacyjne, 2021)
This article was written on the basis of the text created by the author as part of the Polish component of the Reducing Early School Leaving in the EU project carried out within the 7th Framework Program of the European Union for the years 2013-2018. The text was prepared when the author followed a research apprenticeship program at the Faculty of Education of the University of Warsaw. The article describes the teacher’s profession over the past fifteen years, placing special emphasis on teachers’ education, teachers’ careers, rules for and structure of employment.